Keys to successful integration : importance of social relations on the first-phase integration of Burmese refugees in Rovaniemi - Janger, Hanna (2010)
The aim of this study is to find out requirements for successful integration of a specific group of refugees, Burmese, in a Northern Finnish city, Rovaniemi. The research problem is approached by examining the importance of social relations between local volunteer hosts and Burmese refugees. Concentration is on the first-phase integration of the target group. Members of the target group arrived in Rovaniemi in 2007 and were the pilot group for the operations of the project Volunteers Hosting Refugees on the Integration Path. The project recruited and trained local volunteers to operate as volunteer hosts for refugees. These organised social relations were intended to offer social support during the first-phase period of target group’s integration into the new society. Humanitarian based immigration to Finland has been increasing in recent years and this increases the importance of integration policies and practices. Concept of integration, its various interpretations and the connections between integration, social relations and social support are current topics and their importance justifies the implementation of this study. These concepts are subjects for an ongoing political and academic debate and this study brings its input into the public discussion by discussing these concepts in a specific context. Theoretical discussion should not be completely distinguished from the practical environment of everyday life and in this study the practical aspects of first-phase integration are emphasised. This study is implemented as qualitative research and the research problem is approached from the perspective of the target group. Qualitative methods for data collection are used and total of 13 Burmese informants were interviewed. Implemented interviews with Burmese function as the main source for information. Supplementary sources include two interviews with volunteer hosts (four interviewees) and relevant literary products of the project. The results of this study highlight the importance of social relations and expressive and instrumental social support for the integration and wellbeing of immigrants. The practical nature of social support is highlighted in the data. The findings of this study strengthen the results of earlier studies and emphasize that the different backgrounds and needs of refugee groups and individuals should be in central focus when planning integration policies and individual integration plans.